Potential loá of rice landraces from a Terai community in Nepal: a case study from Kachorwa, Bara - Chaudhary, P.=700 1 Gauchan, D.; Rana, R.B.; Sthapit, B.R.; Jarvis, D.I.
(En, Es, Fr)
ilus., 17 ref.
Keywords: ORYZA SATIVA; RECURSOS GENETICOS; CONSERVACION DE LOS RECURSOS; CARACTERISTICAS DEL SITIO; NEPAL